2020
DOI: 10.1016/j.cortex.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Labels strengthen motor learning of new tools

Abstract: Recent reformulations of the Sapir-Whorf hypothesis have shown how labels can guide our thinking in situations of uncertainty, facilitating the identification of objects. We examine whether the effect of labels extends beyond perceptual processes, to help us learn the motoric manipulations required to use novel tools. Exploiting immersive virtual reality, we measured behavioural movement latencies and electrophysiological activity from participants learning to use a range of labeled and unlabeled novel tools. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Semantic representations encode stable properties of tools, for example, sensorimotor properties such as shape and size, which remain rather invariant across contexts as compared with variable properties such as the current object orientation. Hence, language (semantics) contributes to ground conceptual information, such as proposed by the Label Feedback Hypothesis [32], and plays a direct role in motor learning [33]. For instance, it has been shown that reading verbs related to actions and functions induces a person to process affordances of objects close to their body faster than those distant from it, while reading verbs related to observing and pointing does not lead to any difference (e.g., [34,35]).…”
Section: Affordances In Different Physical Linguistic and Social Contextsmentioning
confidence: 99%
“…Semantic representations encode stable properties of tools, for example, sensorimotor properties such as shape and size, which remain rather invariant across contexts as compared with variable properties such as the current object orientation. Hence, language (semantics) contributes to ground conceptual information, such as proposed by the Label Feedback Hypothesis [32], and plays a direct role in motor learning [33]. For instance, it has been shown that reading verbs related to actions and functions induces a person to process affordances of objects close to their body faster than those distant from it, while reading verbs related to observing and pointing does not lead to any difference (e.g., [34,35]).…”
Section: Affordances In Different Physical Linguistic and Social Contextsmentioning
confidence: 99%
“…Second, an increasing number of studies are showing that language impacts cognition in multiple ways. These studies highlight how language influences not only high-level cognition (e.g., reasoning and problem solving) but also perception, for example helping humans to better recognise and categorise objects and entities 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Possessing a label for a novel object can facilitate learning how to grasp it for use but not how to move it. Language encodes stable properties of tools, thereby contributing to ground conceptual information-as proposed by the Label Feedback Hypothesis [29]-and plays a direct role in motor learning [30]. Reading verbs related to action and functions induces us to process affordances of objects close to our body faster than those distant from it, while reading verbs related to observation and pointing does not lead to any difference [31,32].…”
Section: Affordances and Context Consistently Withmentioning
confidence: 99%